Analysis of RF Stress Influence on Large-Signal Performance of 22nm FDSOI CMOS Transistors utilizing Waveform Measurement - Dang Khoa Huynh; Quang Huy Le; Steffen Lehmann; Zhixing Zhao; Germain Bossu; Wafa Arfaoui; Defu Wang; Thomas Kämpfe; Matthias Ru (2021 16th European Microwave Integrated Circuits Conference (EuMIC), 2021)
The following study employs RF waveform engineering to monitor degradation in 22nm FDSOI transistor at high-frequency region. The current and voltage waveforms are measured, reconstructed, and de-embedded to the device’s intrinsic during large-signal CW RF stress testing. This technique provides extra information on device performance compared with standard DC and RF figures of Merits degradation. With clear pictures of where on the output IV plane the degradation is occurring, device designers can get an insight into the degradation behavior limiting RF performance. It is observed that devices show a different behavior under RF stress in comparison to DC-stress-induced degradation.